Investment, R&D and financial constraints in Britain and Germany - Steve Bond; Dietmar Harhoff; John Van Reenen (Institute for Fiscal Studies (IFS), 1999)
This paper tests for the importance of cash flow on investment in fixed capital and R&D using firm-level panel data in two countries between 1985 and 1994. For German firms, cash flow is not informative in simple econometric models of fixed investment or R&D. In identical pecifications for British firms, cash flow is informative about investment, although not about the level of R&D spending conditional on the R&D participation decision. In the UK, we also find that investment is less sensitive to cash flow for R&D-performing firms, and that cash flow predicts whether firms perform R&D or not. We confirm that these differences do not simply reflect a greater role for current cash flow in forecasting future sales. These results suggest that financial constraints are more significant in Britain, that they affect the decision to engage in R&D rather than the level of R&D spending by participants, and that consequently the British firms that do engage in R&D are a self-selected group where financing constraints tend to be less binding.
Keywords: O31; C25; L13; 330